Initiation of Apoptosis and Autophagy by the Bcl-2 Antagonist HA14-1 - Kessel, David (2006)
L1210 murine leukemia cells exposed to an LD(90) concentration of the Bcl-2/Bcl-x(L) antagonist HA14-1 rapidly undergo apoptosis but also develop numerous intracellular vacuoles with double membranes, exhibit enhanced labeling by monodansylcadaverine, and convert the cytosolic protein LC3-I to LC3-II. These are hallmarks or autophagy. Autophagic vacuoles develop rapidly, preceding the appearance of an apoptotic nuclear morphology and can be observed in both non-apoptotic and apoptotic cells. Inhibition of autophagy by the PI 3-kinase inhibitor wortmannin promoted apoptosis; conversely inhibition of caspase-3/7 with zDEVD-fmk promoted autophagy. Neither process was dependent on calcium translocation. These results indicate that pharmacological suppression of Bcl-2 function can mimic the induction of autophagy that can occur following the down-regulation of Bcl-2 expression by molecular approaches.